Reduced Cell Excitability of Cardiac Postganglionic Parasympathetic Neurons Correlates With Myocardial Infarction-Induced Fatal Ventricular Arrhythmias in Type 2 Diabetes Mellitus - Hu, Wenfeng; Zhang, Dongze; Tu, Huiyin; Li, Yu-Long (Frontiers in Neuroscience, 2021)
Objective: Withdrawal of cardiac vagal activity is considered as an important trigger for acute myocardial infarction (MI)-induced ventricular arrhythmias in type 2 diabetes mellitus (T2DM). Our previous study demonstrated that cell excitability of cardiac parasympathetic postganglionic (CPP) neurons were reduced in T2DM rats. This study investigated whether cell excitability of CPP neurons is associated with cardiac vagal activity and MI-induced ventricular arrhythmias in T2DM rats. Methods: Rat T2DM was induced by a high-fat diet plus streptozotocin injection. MI-evoked ventricular arrhythmia was achieved by surgical ligation of the left anterior descending coronary artery. Tween four-hour continuous ECG recording was used to quantify ventricular arrhythmic events and heart rate variability (HRV) in conscious rats. The power spectral analysis of HRV was used to evaluate autonomic function. Cell excitability of CPP neurons was measured by the whole-cell patch-clamp technique. Results: 24-h ECG data demonstrated that MI-evoked fatal ventricular arrhythmias are more severe in T2DM rats than that in sham rats. As a result, the Kaplan-Meier analysis demonstrated that the survival rate over 2 weeks after MI is significantly reduced in T2DM rat, compared with sham rat. The susceptibility to ventricular tachyarrhythmia elicited by programmed electrical stimulation was higher in anesthetized T2DM plus MI rats than that in rats with MI or T2DM alone. Additionally, T2DM increased heterogeneity of ventricular electrical activities, blunted vagal control of the ventricular function, and reduced cardiac parasympathetic activity and cell excitability of CPP neurons. However, MI did not alter vagal control of the ventricular function and CPP neuronal excitability although it also induced cardiac autonomic dysfunction and enhanced heterogeneity of ventricular electrical activities. Conclusion: The reduction of CPP neuron excitability is involved in decreased cardiac vagal activity, which is associated with MI-induced high mortality and malignant ventricular arrhythmias in T2DM.